HUBUNGAN KECERDASAN EMOSIONAL DAN KEPERCAYAAN DIRI DENGAN TINGKAT PEMAHAMAN AKUNTANSI SISWA SMK - Rohman Arif Raynaldy; siswandari siswandari; Asri Diah Susanti (Universitas Sebelas Maret, 2020)
AbstractThe study aimed to examine: 1) the correlation between the emotional quotient with the level of understand of accounting students of Vocational High School; 2) the correlation between self-confidence with the level of understand of accounting students of Vocational High School; 3) the correlation between emotional quotient and self-confidence with the level of understand of accounting students of Vocational High School. The research method used in this study is a quantitative method. The population in this study were all the student class X and XI of Accounting majors of Vocational High School. From the population, then a sample of 174 students was taking stratified proportional random sampling technique. Data collection techniques used in this study are using questionnaires. Data analysis techniques using descriptive statistical analysis and inferential analysis (prerequisite test analysis and hypothesis testing). The validity of the data was obtained through validity and reliability testing. The results of this study showed that: First, there was a positive and significant correlation between the emotional quotient with the level of understand of accounting students of Vocational High School. Second, there was a positive and significant correlation between self-confidence with the level of understand of accounting students of Vocational High School. Third, there was a positive and significant correlation between emotional quotient and self-confidence with the level of understand of accounting students Vocational High School.Keywords: Emotional Quotient, Self Confidence, Understand of Accounting AbstrakPenelitian ini bertujuan untuk menguji: 1) hubungan kecerdasan emosional dengan tingkat pemahaman akuntansi siswa SMK; 2) hubungan kepercayaan diri dengan tingkat pemahaman akuntansi siswa SMK; 3) hubungan kecerdasan emosional dan kepercayaan diri dengan tingkat pemahaman akuntansi siswa. Metode penelitian yang digunakan dalam penelitian ini adalah metode kuantitatif. Populasi dalam penelitian ini yaitu siswa kelas X dan XI jurusan Akuntansi SMK. Sampel yang diambil dari populasi penelitian sejumlah 174 siswa menggunakan teknik stratified proportional random sampling. Teknik pengambilan data yang digunakan dalam penelitian ini yaitu menggunakan angket dan soal tes. Teknik analisis data menggunakan analisis statistik deskriptif dan analisis inferensial (uji prasyarat analisis dan uji hipotesis). Keabsahan data diperoleh melalui uji validitas dan uji reliabilitas. Hasil penelitian ini adalah sebagai berikut: Pertama, terdapat hubungan yang positif dan signifikan antara kecerdasan emosional dengan tingkat pemahaman akuntansi siswa SMK. Kedua, terdapat hubungan yang positif dan signifikan antara kepercayaan diri dengan tingkat pemahaman akuntansi siswa SMK. Ketiga, terdapat hubungan yang positif dan signifikan antara kecerdasan emosional dan kepercayaan diri dengan tingkat pemahaman akuntansi siswa SMK. Kata kunci: Kecerdasan Emosional, Kepercayaan Diri, Pemahaman Akuntansi